Peran Guru Dalam Mengembangkan Kemampuan Motorik Halus Di Era New Normal Kelompok B Usia 5-6 Tahun Di Tk Berlian Biontong 1 Kecamatan Bolangitang Timur Kabupaten Bolaang Mongondow Utara - Astri Latarima; Nunung Suryana Jamin; Rapi Us Djuko; Sri Rawanti; Sulastya Ningsih (Early Childhood Education Department, Faculty of Education, State University of Gorontalo, 2022)
The formulation of the problem in this research is how teachers can develope fine motor skills in the new normal era for group B aged 5-6 years Berlian Biontong 1 Kindergaten east Bolangitang District, North Bolaang Mongondow Regency. This study aims to determine the role of techers in developing fine motor skills in the new normal era. This study uses a qualitative method. Dat collection was carried out by observational interviews and documentation. the results of the research on the role of teachers in developing fine motor skills in the new normal era group B aged 5-6 years at Berlian Biontong 1 kindergraten, east Bolangitang District, North Bolaang Monggondow Regency . Namely the role of the teacher as a planner, in the indicator of the teacher’s role as a planner the teacher makes learing refrerences not only using rpph but also making recommendations made from schools to be distributed to parents of students as a reference in developing children’s learning abilities in this case, namely parents and teacher work together in developing children’s learning abillities, in this case, where parents and teachers work together in developing children’s fine motor skills seeing now that they are still in the covid-19 epidemic period. Keywords: teacher role, fine motor in the new normal era.